ALLAH BERBICARA MELALUI MIMPI (AYUB 33:13-18) - Tantiono, Paulus Toni (UNIKA Santo Thomas, 2004)
The lamentation of Job (Job 31:35) needed to be answered by God, whom Job considered extremely unjust by causing great sufferings into his life. His three closed friends (Eliphaz, Bildad and Zophar) were rather his enemies in defending the traditional thesis of retribution. Although he pleaded against God, he found no answer from God. In his desperation, finally, Job appealed to a legal metaphor against God, and in this moment Elihu appeared as an arbiter, who presupposed to judge Job in Godâ€™s stead, and tried to respond to Jobâ€™s requests in judicial style. Elihu tried to convince Job that God did hear his lamentation and answered him. Only Job could not hear it, since God was greater than human beings and He answered in unpredictable ways, in this case He was talking â€œthrough dreamsâ€ as â€œa divine revelationâ€. Dream was Godâ€™s effort to turn Job from wrongful deeds or pride (Jobâ€™s arrogance in assuming complete integrity before God). It tended to warn Job to change his attitude into a faithful life.